Development Of Tetragonal Zirconia Thin Film For Semiconductor Application - Chan, Pooi Quan (2011)
In this work, the YSZ and Nb-YSZ film were produced by using chemical solution deposition (CSD) technique via dip coating. The films were deposited on two different substrates (silica glass and Si wafer). Various parameters were conducted in this study including numbers of coatings, concentration of precursor solution, annealing temperature and heating rate to obtain the optimum condition for coating of the film. The precursor solution was prepared with the molar ratio of ZrOCl2·8H2O to YNO3·6H2O at 95:5 and mixed with absolute ethanol as a solvent.